Das Problem der Linken mit der Technik: Ein Zwischenruf aus dem Maschinenraum - Frings, Christian (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2017)
Within the left discourse concerning technology there is a tendency to regard new technologies like the computer and the internet either as blessing or as curse. While some scholars are suggesting that the new so called digital economy is leading us to a new post-capitalist society ruled by a “general intellect”, others fear that “big data” and digital control will inevitably strengthen the power of state and capital. The article uses Marx’ critique of capital as a fetish as a framework and argues that the blessing-curse-discourse is – on both sides – only replicating the fetish character instead of criticizing it. The critical discourse about technology should focus more on the relationship between new forms of struggles linked to new technologies, leave the walled off academic sphere, and abandon the blessing-curse-debate.